JenangLagi: Pemanfaatan ampas apel manalagi melalui proses fortifikasi menjadi produk pangan untuk mencegah radikal bebas - Az-Zahra, Luthfia Cahya (Maliki Interdisciplinary Journal, 2024)
In Indonesia, apples are the leading commodity in Batu City, Malang, East Java, which is in the highlands. Apples contain fiber and several types of phytochemicals that are beneficial for health. In the apple cider processing industry, the remaining apple waste is only used for animal feed and fertilization, even though apple pulp still contains chemical contents that are beneficial for health. Producing apple pulp into jenang is a form of innovation and added value. To increase the nutritional quality, fortification is carried out to increase the nutritional quality of jenang. Fortifying apple pulp with yogurt will add health benefits to avoid various diseases caused by free radicals and decreased immunity.